Human Rights and Digital Technology - Perry, Susan. author. aut Link
XII, 203 p. 3 illus. in color.
Keywords: Analysing the convergence of law and regulation with rapidly evolving communications technologies, this interdisciplinary work navigates the intricate balancing act between human rights protection and technological innovation in a digital age, and illuminates the comprehensive potential of human rights to frame our intelligent use of technology. The authors address such pressing questions as how to protect user privacy online, whether digital pollution is a health hazard, who should have control and be responsible for data technologies and how to maintain human autonomy in a world of interconnected objects. By considering specific cases, this book provides an in-depth exploration of the many regulatory and technological choices citizens, states, civil society organizations and the private sector should consider to ensure that digital technology more fully serves human needs.